Bright star shining : poems for Christmas - Harrison, Michael, 1939-; Stuart-Clark, Christopher (Grand Rapids, Mich. : Eerdmans Books for Young Readers, 1998)
A collection of poems celebrating the joy and wonder of the Christmas season.
Originally published: Oxford : Oxford University Press, 1993.
Includes index.
Booklist.
4.5
3-6
Keywords: Christmas -- Juvenile poetry; Christmas -- Poetry; Christmas -- Poetry; Christmas -- Poetry